2021
DOI: 10.3390/cancers13102295
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Induced Obesity Impairs Outcomes and Induces Multi-Factorial Deficiencies in Effector T Cell Responses Following Anti-CTLA-4 Combinatorial Immunotherapy in Renal Tumor-Bearing Mice

Abstract: Associations between modifiable factors and the efficacy of cancer immunotherapies remain uncertain. We found previously that diet-induced obesity (DIO) reduces the efficacy of an immunotherapy consisting of adenovirus-encoded TRAIL plus CpG oligonucleotide (AdT/CpG) in mice with renal tumors. To eliminate confounding effects of diet and determine whether outcomes could be improved in DIO mice, we evaluated AdT/CpG combined with anti-CTLA-4 in diet-matched, obese-resistant (OB-RES) versus DIO tumor-bearing mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Intriguingly, immune checkpoint blockade with an anti-CTLA-4 antibody shows a differential response between obese mice cohorts ( 61 , 62 ). In an orthotopic model of renal cell carcinoma, diet-induced obese (DIO) mice showed no therapeutic anti-tumour response to anti-CTLA-4 therapy.…”
Section: Lessons From Cancer Immunotherapymentioning
confidence: 99%
“…Intriguingly, immune checkpoint blockade with an anti-CTLA-4 antibody shows a differential response between obese mice cohorts ( 61 , 62 ). In an orthotopic model of renal cell carcinoma, diet-induced obese (DIO) mice showed no therapeutic anti-tumour response to anti-CTLA-4 therapy.…”
Section: Lessons From Cancer Immunotherapymentioning
confidence: 99%
“…Notably, evaluations of obese-resistant mice that had been fed the same high fat diet for 20 weeks illustrated that host obesity, and not the high fat diet or its components, was the cause of diminished immunotherapeutic efficacy, because obese-resistant mice responded as well to this combination therapy as did control mice on a low-fat chow diet ( 18 ). More recently, we found that obesity-associated defects in T cell responses extended to the intratumoral CD4+ compartment and CD8+ T cells in tumor-draining lymph nodes in mice with renal tumors that were treated with combinatorial anti-CTLA-4 ( 27 ). In 2021, Kheum et al reported that a combinatorial immunotherapy consisting of anti-PD-1/anti-CTLA-4/anti-LAG-3 was less effective in obese mice fed a Western Diet than in age-matched lean controls on standard diet in both the B16 melanoma and MC38 colon carcinoma models ( 28 ).…”
Section: Obesity-associated Changes In Anti-tumor Immunitymentioning
confidence: 99%